Microorganisms in the oribatid mite Hermannia gibba (C. L. Koch, 1839) (Acari: Oribatida: Hermanniidae) - Liana, Marcin; Witaliński, Wojciech (Biological Letters, 2011)
Symbiotic microorganisms associated with arthropods are known to play a significant role in the life of their hosts. Most commonly, the symbionts improve their host's food digestion and modify their meiosis/reproduction. The usual mode of parent-to-offspring transmission of the symbionts is transovarial transmission (vertical) via oocytes. Using transmission electron microscopy, we found extracellular yeast-like and bacteroid microorganisms in food boli, as well as intracellular symbiotic bacteria within cells of the digestive tract and in reproductive cells in both sexes of the oribatid mite Hermannia gibba. In the digestive tract, the scarce bacteria were lying individually within midgut cells. The bacteria observed in developing oocytes were numerous and formed large aggregates close to the nuclear envelope and clusters of mitochondria. In spermatocytes we found a few single bacteria located at the cell periphery. The bacteria in the digestive cells may assist in digestion of plant food, whereas the meiotic drive function of the gonad-invading microbes is uncertain. The studied mite species is biparental and its sex ratio is not biased.